L’urbanisation de la ville de Ninh Binh dans le delta du fleuve rouge (Vietnam) : mise en perspective des forces et faiblesses de la gestion du risque d’inondation. - Éric Mottet; Yann Roche (VertigO)
Flood risk management is becoming an issue that is both relevant and sensitive. Even though no one argues about the need for flood risk management, the practices used are often challenged and subject to controversy. This is particularly the case in the Red River Delta, in Vietnam. Flood risks are very important in the area and so they have been for centuries, but the management practices are often considered as being either very positive or very negative. This paper intends to give a full picture on the strengths and weaknesses of current flood risk management practices in the Red River Delta, through the example of the province of Ninh Binh, where fieldwork has been done from 2002 to 2005. Data and observations collected in this province located in the southwestern tip of the Delta underline the contradictions of flood risk management practices in the Red River Delta. The driving force behind these contradictions seems to be a fast economic and demographic development involving short term planning in a region where areas unexposed to flood risk are not many.